Loneliness as a Mediator of Perceived Discrimination and Depression: Examining Education Contingencies. (September 2019) - Lee, Yeonjung; Bierman, Alex
This study examines whether loneliness explains the association between perceived everyday discrimination and depressive symptoms among older adults as well as whether this indirect pathway differs by education. Three waves (2006, 2010, and 2014) of the Health and Retirement Study ( N  = 7, 130) are analyzed with random-effects models that adjust for repeated observations and fixed-effects models that control for all time-stable influences. Everyday discrimination is associated with loneliness and depressive symptoms but more weakly in fixed-effects models. The association between discrimination and loneliness is stronger at low educational attainment, leading discrimination to be indirectly associated with depressive symptoms through loneliness only at low education. The consequences of everyday discrimination for depression in late life are limited to older adults with low education due to education-contingent associations with loneliness. Perceived discrimination may have broad health consequences through loneliness, especially for older adults at low education.